Randomized controlled trial protocol to improve multisensory neural processing, language and motor outcomes in preterm infants - Mary Lauren Neel; Paul Yoder; Pawel J. Matusz; Micah M. Murray; Ashley Miller; Stephanie Burkhardt; Lelia Emery; Kaleigh Hague; Caitlin Pennington; Jessica Purnell; Megan Lightfoot; Nathalie L. Maitre (BMC, 2019)
Abstract Background Premature infants are at risk for abnormal sensory development due to brain immaturity at birth and atypical early sensory experiences in the Neonatal Intensive Care Unit. This altered sensory development can have downstream effects on other more complex developmental processes. There are currently no interventions that address rehabilitation of sensory function in the neonatal period. Methods This study is a randomized controlled trial of preterm infants enrolled at 32-36 weeks postmenstrual age to either standard care or standard care plus multisensory intervention in order to study the effect of multisensory intervention as compared to standard care alone. The study population will consist of 100 preterm infants in each group (total n = 200). Both groups will receive standard care, consisting of non-contingent recorded parent's voice and skin-to-skin by parent. The multisensory group will also receive contemporaneous holding and light pressure containment for tactile stimulation, playing of the mother's voice contingent on the infant's pacifier sucking for auditory stimulation, exposure to a parent-scented cloth for olfactory stimulation, and exposure to carefully regulated therapist breathing that is mindful and responsive to the child's condition for vestibular stimulation. The primary outcome is a brain-based measure of multisensory processing, measured using time locked-EEG. Secondary outcomes include sensory adaptation, tactile processing, speech sound differentiation, motor and language function, measured at one and two years corrected gestational age. Discussion This is the first randomized controlled trial of a multisensory intervention using brain-based measurements in order to explain the causal effects of the multisensory intervention on neural processing changes to mediate neurodevelopmental outcomes in former preterm infants. In addition to contributing a critical link in our understanding of these processes, the protocolized multisensory intervention in this study is therapist administered, parent supported and leverages simple technology. Thus, this multisensory intervention has the potential to be widely implemented in various NICU settings, with the opportunity to potentially improve neurodevelopment of premature infants. Trial registration NIH Clinical Trials (clinicaltrials.gov): NCT03232931. Registered July 2017.